In vivo1H MRS study in microlitre voxels in the hippocampus of a mouse model of Down syndrome at 11.7 T. (1st August 2014) - Santin, Mathieu D.; Valabrègue, Romain; Rivals, Isabelle; Pénager, Romain; Paquin, Raphaël; Dauphinot, Luce; Albac, Christelle; Delatour, Benoit; Potier, Marie‐Claude
<x xml:space="preserve">Abstract</x> In this article, we report in vivo1H MRS performed in 1.8‐μL voxels in a mouse model of Down syndrome (DS). To characterise the excitation–inhibition imbalance observed in DS, metabolite concentrations in the hippocampi of adult Ts65Dn mice, which recapitulate features of DS, were compared with those of their euploid littermates at a voxel 42‐fold smaller than in a previously published study. Quantification of the metabolites was performed using a linear combination model. We detected 16 metabolites in the right and left hippocampi. Principal component analysis revealed that the absolute concentrations of the 16 detected metabolites could differentiate between Ts65Dn and euploid hippocampi. Although measurements in the left and right hippocampi were highly correlated, the concentration of individual metabolites was sometimes significantly different in the left and right structures. Thus, bilateral values from Ts65Dn and euploid mice were further compared with Hotelling's test. The level of glutamine was found to be significantly lower, whereas myo‐inositol was significantly higher, in the hippocampi of Ts65Dn relative to euploid mice. However, γ‐aminobutyric acid (GABA) and glutamate levels remained similar between the groups. Thus, the excitation–inhibition imbalance described in DS does not appear to be related to a radical change in the levels of either GABA or glutamate in the hippocampus. In conclusion, microliter MRS appears to be a valuable tool to detect changes associated with DS, which may be useful in investigating whether differences can be rescued after pharmacological treatments or supplementation with glutamine. Copyright © 2014 John Wiley & Sons, Ltd.